A Harmonic Suppression Method for the Single Phase PWM Rectifier in the Hydrogen Production Power Supply - Li Lun; Siming Chen; Yihe Zhan; Hui Yang; Jianyong Zhu (Applied Sciences)
In renewable and sustainable hydrogen production energy systems (RSHPES), the presence of harmonics gives rise to fluctuations in the voltage and current of the electrolysis cell (EC). This, in turn, results in an unstable electrolysis process, a reduction in hydrogen production efficiency, and an escalation in electrode corrosion. This paper puts forward a novel harmonic suppression control method (HSCM), which is devised for the single phase PWM rectifier in hydrogen production rectifiers (HPR) with the aim of alleviating the adverse impacts caused by harmonics. Initially, a highly meticulous harmonic model is constructed, which lays solid groundwork for understanding the existing problems. Subsequently, a comprehensive and detailed explanation of the HSCM is provided, accentuating its novel and inventive strategy for harmonic suppression. Thereafter, a comparison is drawn between the HSCM and traditional methods, thereby manifesting its enhanced suitability and superiority within the context of RSHPES. In conclusion, the simulation and experimental results vividly demonstrate the advantages, effectiveness, and practicality of HSCM under four conditions of power grids containing integer multiples of harmonics, interharmonics, ultraharmonics, and voltage disturbances.